Polymorphisms in base excision repair genes and thyroid cancer risk - Santos, Luís S. (2021)
Thyroid cancer (TC) is the most frequent endocrine malignancy, accounting however for only 1-2% of all human cancers, and the best-established risk factor for TC is radiation exposure, particularly during childhood. Since the BER pathway seems to play an important role in the repair of DNA damage induced by IR and other genotoxicants, we carried out a hospital-based case-control study in order to evaluate the potential modifying role of 6 BER polymorphisms on the individual susceptibility to non-familial TC in 109 TC patients receiving iodine-131, and 217 controls matched for age (±2 years), gender and ethnicity. Our results do not reveal a significant involvement of XRCC1 Arg194Trp and Arg399Gln, OGG1 Ser326Cys, APEX1 Asp148Glu, MUTYH Gln335His and PARP1 Val762Ala polymorphisms on the individual susceptibility towards TC, mostly in aggreement with the limited available evidence. By histological stratification analyis, we observed that the association between the presence of heterozygozity in the MUTYH Gln335His polymorphism and TC risk almost reached significance for the papillary subtype of TC. This was the first time that the putative association between this polymorphism and TC susceptibility was evaluated. However, since the sample size was modest, the possibility of a type I error should not be excluded and this result should, therefore, be interpreted with caution. More in depth studies involving larger populations should be pursued in order to further clarify the potential usefulness of the MUTYH Gln335His genotype as a predictive biomarker of susceptibility to TC and the role of the remaining BER polymorphisms on TC susceptibility.